A política pública da educação do campo em Feira de Santana: entre o dizer e o fazer - Lima, Rosângelis Rodrigues Fernandes (2014)
This current text, the result of an academic research developed in PPGE – UEFS Masters in Education, analyzes the issue about Rural Education, as well as, how the national public policy for Rural Education has been developed in Feira de Santana, in a municipal school, located in the community of Matinha dos Pretos. During the study, the research sought to answer questions related to the developments and meanings of the national public policy for Rural Education of Feira de Santana. It also sought to reveal the meaning of what is meant by education as a process of humanization, and human development, to understand Rural Education. However, to comprehend the Rural Education in the historical period from 2002 to 2013, it became necessary to investigate it‟s essence from the struggles of social movements and agrarian reform. In the discussions between the documents and the contents about Rural Education, it attempted to present and understand the following categories: State, Public Policy, Education, Social Movements, Labor, Education, Human Development and Rural Education. This text is configured as a social research focusing on the qualitative approach using the tools of data collecting such as observation and interviews. It can be placed as a social, political and scientific relevant work, because it discuss Rural Education as well as the public policy for Rural Education implementation, more specifically, in the district of Matinha dos Pretos. This text dialogues with authors who discuss Rural Education and it‟s contradictions and conflicts based on Historical Dialectical Materialism. The data analysis indicated through the voices of the participating subjects of the research, showed that Feira de Santana‟s Rural Education doesn't obey the specificities of the people who live in the countryside, as well as, revealed that the actions made for the national public policy of Feira de Santana's Rural Education don't really happen in an explicit way.